Long-term performance of implant-supported metal-ceramic and all-ceramic single crowns - Rammelsberg, Peter; Lorenzo Bermejo, Justo; Kappel, Stefanie; Meyer, André; Zenthöfer, Andreas (Journal of prosthodontic research, 2020)
Purpose - To evaluate failure rates and incidence of chipping for metal-ceramic and all-ceramic implant-supported single crowns (SCs). - Methods - Six hundred and fifty-two implant-supported SCs placed in 404 patients (mean age: 57.8 years; 193 male; mean SCs per patient: 1.6) were evaluated up to 12.8 years. The frameworks of the SCs were made from Au alloys (n = 319), CoCr (n = 37), zirconia (n = 286), or lithium disilicate (n = 10). Full-coverage ceramic veneers were placed on 319 Au SCs, 34 CoCr SCs, and 92 zirconia SCs. One hundred and fifty-two monolithic zirconia SCs were not veneered. A partial veneer was placed on the buccal surface only of a further 42 zirconia SCs. - Results - A total of 26 failures were caused by loss of implants (n = 6), ceramic fractures and chipping (n = 15), loosening of the abutment (n = 4), or swallowing of a de-cemented SC (n = 1). Kaplan-Meier analysis revealed a probability of survival of 96% after five years and 92% after 10 years. A greater incidence of failure was observed for lithium disilicate and zirconia SCs than for metal-ceramic SCs (p < .05). Separate analysis of the most frequent complication, chipping (n = 61), revealed that zirconia and lithium disilicate frameworks were significant risk factors for chipping (p < 0.05). Furthermore, a significantly greater incidence of chipping was observed for SCs with full-coverage veneers than for monolithic zirconia SCs and for SCs with partial veneers (p < .05). - Conclusion - Avoidance of full-coverage veneers significantly improves the clinical performance of implant-supported crowns, primarily reduces the incidence of chipping.
Available online 16 December 2019
Gesehen am 04.08.2020